Socio Cultural Taboos and Restrictions during Menstruation followed by School going Adolescent Girls in a Semi Urban Area of Jaipur, Rajasthan - Hossain, Samar; Sen, Vandna (Journal of Pharmacy Practice and Community Medicine)
Objective: With this background the present study was designed as an attempt to unfurl the taboos related to menstruation prevalent amongst school going adolescent girls in a rural area. Methods: The present study was conducted among girl’s middle and high schools of Achrol village which is a rural field practice area (RHTC) of NIMS. Study population included all adolescent school going girls of 10-19 years age group residing in Achrol vilage, Jaipur. Results: The study concluded that out of the 400 girls selected for the study, 325 were not allowed to enter the kitchen or cook food during menstruation. A majority i.e. 85% of the adolescent girls were not allowed to touch the pickle jar. Conclusion: It was concluded that unless the myths, misconceptions and customs which go against the girl child are changed it will be difficult to improve the nutritional, health, economic and social status of the girls.
Keywords: Menstruation; Adolescent girls; Taboos; Beliefs; Patterns